A systematic review of the diagnostic accuracy of natriuretic peptides for heart failure. - Doust, J; Glasziou, P; Pietrzak, E; Dobson, A (2004)
BACKGROUND: The diagnosis of heart failure is difficult, with both overdiagnosis and underdiagnosis occurring commonly in practice. Natriuretic peptides have been proposed as a possible test for assisting diagnosis. We assessed the diagnostic accuracy of brain natriuretic peptide (BNP), including a comparison with atrial natriuretic peptide (ANP). METHODS: Electronic searches were conducted of MEDLINE and EMBASE from January 1994 to December 2002 and handsearches of reference lists of included studies. We included studies that assessed the diagnostic accuracy of BNP against echocardiographic or clinical criteria or that compared the diagnostic accuracy of BNP with ANP. Two reviewers assessed studies for inclusion and quality and extracted the relevant data. A meta-analysis was performed by pooling the diagnostic odds ratios for studies that used a common reference standard. RESULTS: Twenty studies were included. For the 8 studies (n = 4086) that measured BNP against the criterion of left ventricular ejection fraction of 40% or less (or equivalent), the pooled diagnostic odds ratio was 11.6 (95% confidence interval, 8.4-16.1). The pooled diagnostic odds ratio was greater, 30.9 (95% confidence interval, 27.0-35.4), in the 7 studies (n = 2374) that measured BNP against clinical criteria (generally a consensus view using all other clinical information). The diagnostic odds ratio was similar in studies conducted in general practice and in hospital settings. Three studies compared BNP with N-terminal-ANP, a precursor form of ANP, and pooling of the results of these studies showed BNP to be a more accurate marker of heart failure than NT-ANP. CONCLUSIONS: Brain natriuretic peptide is an accurate marker of heart failure. Use of a cutoff value of 15 pmol/L achieves high sensitivity, and BNP values below this exclude heart failure in patients in whom disease is suspected. As the diagnostic odds ratio for BNP is greater when assessed against clinical criteria than against left ejection fraction alone, BNP may also be detecting patients with "diastolic" heart failure.